Characterization of silences acid dosimeter for gamma-radiation dosimetry - Abul –Hail, Riyadh. CH. (University of Thi-Qar Journal of Science, 2014)
Silences acid has been investigated as a dosimeter for high doses of Gamma radiation through measuring the induced changes in optical absorbance from (315-900) nm at room temperature. It was found that the absorbance increased with increasing absorbed Gamma-dose. Also, the dose rate and post irradiation fading of optical absorption spectra has been studied. The results of this preliminary study show that Silences acid may be applied as a simple optical absorbance detector for dose measurement in the dose range (5 - 28 ) kGy.